Installation effects and self diagnostics for ultrasonic flow measurement - Carlander, Carl (Luleå tekniska universitet, EISLAB, 2001)
In the district heating industry, heat meters, consisting among other things of a flow meter, are used for billing purpose. The district heating industry desires accurate and low cost flow measurements. There are mainly two reasons. An under estimation of the flow rate leads to a loss of income for the district heating industry. Further, the total cost for measuring, including the cost for the heat meter, the reading and the maintenance, represents a relatively large part of the total energy cost. Therefore a project concerning measurement quality assurance in district heating systems is in progress at Luleå University of Technology. As a part of this project the possibility of self diagnostic techniques for flow meters is investigated. It is well known that installation effects greatly impair the flow measurement involved in heat metering. Thus this thesis focus on self diagnostics of different installation effects. The basic assumption is that the flow meter noise level is correlated to turbulence intensity. Since the turbulence intensity is effected by installation effects, the noise level can be used to detect conditions for which the flow meter shows erroneous results. In district heating applications the use of ultrasonic flow meters are becoming more and more frequent. The self diagnostic approach has therefore been investigated for a small size prototype ultrasonic flow meter. Single and double elbow pipe bends and pipe diameter reductions mounted in front of the meter and pulsating flow give rise to small but reproducible errors. The magnitude of the maximum errors were in the range of 2 to 4% of flow rate. At low flow rates with pulsating flow the errors were larger. Also small commercial ultrasonic flow meters were investigated. These commercial meters are commonly used in heat meters in small district heating subscriber stations. The results demonstrate that both temperature changes and installation effects introduce errors in the flow measurements. By studying the noise level of the signal from the ...